Analisis Tingkat Kesukaan Konsumen terhadap Minuman Kekinian “Coconut Shake” - Eddy Roesdiono; Anggi Avita Da Tista (Syntax Corporation Indonesia, 2025)
Along with the development of the times, beverage products began to have many variations. Coconut Shake is a trending drink in Singapore made from coconut, milk, and various flavors. The purpose of this organoleptic test research is to find out the level of preference seen from the taste, aroma, and color of Coconut Shake products and to find out the public acceptance of Coconut Shake products. The results of the study showed that 5 respondents liked the contemporary drink